2018
DOI: 10.7554/elife.40251
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic drive of female-inherited supernumerary chromosomes in a pathogenic fungus

Abstract: Meiosis is a key cellular process of sexual reproduction that includes pairing of homologous sequences. In many species however, meiosis can also involve the segregation of supernumerary chromosomes, which can lack a homolog. How these unpaired chromosomes undergo meiosis is largely unknown. In this study we investigated chromosome segregation during meiosis in the haploid fungus Zymoseptoria tritici that possesses a large complement of supernumerary chromosomes. We used isogenic whole chromosome deletion stra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 56 publications
1
42
0
Order By: Relevance
“…While beneficial effects, even if they are comparably small, might explain the maintenance of accessory chromosomes in Z. tritici populations, negative effects as observed in this study and reported by Habig et al (2017) raise the question why these chromosomes have not been lost over time, especially as they can easily be lost during meiosis and mitosis. Accessory chromosome can be lost during meiosis ( Wittenberg et al 2009 ), but interestingly accessory chromosomes have also been shown to follow non-Mendelian segregation and to be transmitted at a significantly higher rate than expected, if one of the two mating partners lacks an accessory chromosome ( Fouché et al 2018 ; Habig et al , 2018 ). While there is no comprehensive mechanistic explanation yet, chromosome conservation by re-replication during meiosis may counteract the chromosome loss during vegetative growth and therefore maintain accessory chromosomes in pathogen populations.…”
Section: Discussionmentioning
confidence: 99%
“…While beneficial effects, even if they are comparably small, might explain the maintenance of accessory chromosomes in Z. tritici populations, negative effects as observed in this study and reported by Habig et al (2017) raise the question why these chromosomes have not been lost over time, especially as they can easily be lost during meiosis and mitosis. Accessory chromosome can be lost during meiosis ( Wittenberg et al 2009 ), but interestingly accessory chromosomes have also been shown to follow non-Mendelian segregation and to be transmitted at a significantly higher rate than expected, if one of the two mating partners lacks an accessory chromosome ( Fouché et al 2018 ; Habig et al , 2018 ). While there is no comprehensive mechanistic explanation yet, chromosome conservation by re-replication during meiosis may counteract the chromosome loss during vegetative growth and therefore maintain accessory chromosomes in pathogen populations.…”
Section: Discussionmentioning
confidence: 99%
“…Further, even fewer of these present opportunity for experimentation which will lead to a deeper and more concrete understanding of the evolution of GS. Such an ambitious approach, which has been successfully employed in at least one pathogenic fungal species, revealed that accessory chromosomes which exhibit meiotic drive [123] are also associated with genome instability and an increase in virulence and fitness [124]. Here, I consider a further few promising model systems for testing the causality of these correlations through direct manipulation of both the environment and GS, to see the outcome on a phenotypic level.…”
Section: Potential Model Organisms For Genome Size Evolutionmentioning
confidence: 99%
“…The haploid genome of the reference isolate IPO323 comprises thirteen core and eight accessory chromosomes [23]. Some of these accessory chromosomes may encode traits that impact virulence of the fungus, however no gene encoded on an accessory chromosome has so far been described as a virulence or avirulence determinant [24][25][26][27][28][29]. Interestingly, the accessory chromosomes in Z. tritici show a low transcriptional activity in vitro as well as in planta [30,31].…”
Section: Introductionmentioning
confidence: 99%